2007
DOI: 10.1172/jci28833
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibition enhances therapy-induced apoptosis in a Myc-induced model of lymphoma

Abstract: Autophagy is a lysosome-dependent degradative pathway frequently activated in tumor cells treated with chemotherapy or radiation. Whether autophagy observed in treated cancer cells represents a mechanism that allows tumor cells to survive therapy or a mechanism for initiating a nonapoptotic form of programmed cell death remains controversial. To address this issue, the role of autophagy in a Myc-induced model of lymphoma generated from cells derived from p53ER(TAM)/p53ER(TAM) mice (with ER denoting estrogen re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
841
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 1,031 publications
(894 citation statements)
references
References 51 publications
47
841
0
6
Order By: Relevance
“…105 Other studies, however, support the use of autophagy inhibitors as potentiators of anticancer agents. 106,107 As an example, the mammalian target of rapamycin (mTOR) kinase inhibitor everolimus, which induces autophagy, prolonged the survival of patients affected by renal cell carcinoma in a phase-III clinical trial. 106 Interestingly, Michaud et al 108 reported that autophagy is dispensable for chemotherapy-induced TCD, but is required for its immunogenicity.…”
Section: Effects On Tumor Cells and On Tumor Microenvironmentmentioning
confidence: 99%
“…105 Other studies, however, support the use of autophagy inhibitors as potentiators of anticancer agents. 106,107 As an example, the mammalian target of rapamycin (mTOR) kinase inhibitor everolimus, which induces autophagy, prolonged the survival of patients affected by renal cell carcinoma in a phase-III clinical trial. 106 Interestingly, Michaud et al 108 reported that autophagy is dispensable for chemotherapy-induced TCD, but is required for its immunogenicity.…”
Section: Effects On Tumor Cells and On Tumor Microenvironmentmentioning
confidence: 99%
“…Low levels of autophagic activity are observed under physiological conditions, while in tumor cells, autophagy promotes cell survival during the frequent nutrient restriction and hypoxia [49]. Autophagy was found to sustain the maintenance of cancer stem cell phenotype, and cooperates to chemo-and radio-resistance [50][51][52][53]. Inhibition of autophagy, on the contrary, increases chemo-and radio-sensitivity [54].…”
Section: How Low Ph May Contribute To Dormancy Of Tumor Cells Aciditymentioning
confidence: 99%
“…80,81,82 Hence, more efforts should be made to elucidate the intricate interaction between autophagy inhibition and resulting effects on the immunogenicity.…”
Section: Autophagic Cell Deathmentioning
confidence: 99%